2018
DOI: 10.1021/acssynbio.8b00115
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Model-Based Analysis, and Characterization of a Promoter Library for Fine-Tuned Gene Expression in Bacillus subtilis

Abstract: Promoters are among the most-important and most-basic tools for the control of metabolic pathways. However, previous research mainly focused on the screening and characterization of some native promoters in Bacillus subtilis. To develop a broadly applicable promoter system for this important platform organism, we created a de novo synthetic promoter library (SPL) based on consensus sequences by analyzing the microarray transcriptome data of B. subtilis 168. A total of 214 potential promoters spanning a gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 65 publications
0
67
0
Order By: Relevance
“…In addition to these host-modification strategies to improve the cellular performance, some gene regulation and expression methods have also been applied to increase protein production. In recent years, a great amount of fundamental work on promoters has been undertaken, and various promoters have been identified and reconstructed to achieve high-level expression of recombinant proteins, with some notable results [9][10][11]. Although transcription is the first and key step in the process of gene expression [12], the transcriptional effectiveness of one promoter varies for different proteins, and the so-called optimal promoter sequences cannot be generalized for all heterologous enzymes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these host-modification strategies to improve the cellular performance, some gene regulation and expression methods have also been applied to increase protein production. In recent years, a great amount of fundamental work on promoters has been undertaken, and various promoters have been identified and reconstructed to achieve high-level expression of recombinant proteins, with some notable results [9][10][11]. Although transcription is the first and key step in the process of gene expression [12], the transcriptional effectiveness of one promoter varies for different proteins, and the so-called optimal promoter sequences cannot be generalized for all heterologous enzymes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jensen et al 13 revealed a simple statistical method to explore nucleotide positions, which exerted critical effect on promoter intensity in 69 PL-λ promoter variants in E. coli. Likewise, Mey et al 14 and Liu et al 17 observed similar results by analyzing a partial least squares (PLS) model in E. coli and Bacillus subtilis using 49 and 214 synthetic promoters, respectively. However, these reports suffered small data issues, single modeling, imperfect correlations and low dynamic ranges.…”
Section: Introductionmentioning
confidence: 67%
“…The transcriptional intensity ranged from 0.007%-4630% that of the PBAD promoter, and 0.03-2.03-fold that of the P43 promoter at the transcriptional level. However, the strength of these promoters was still not comparative, or far lower than other wellstudied promoters, such as P43 17 , PVeg 17 , PT7, Ptrc 18 , and PThl 19 .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations